Toward an Ecological Understanding of Agriculture: Why Diversity Matters - Harris, Wylie N; Vogeleang, Keith M (Annals of Arid Zone, 2016)
Faced with heightened pressures for increased food production to keep pace with growing’ human populations, current modes of industrial agriculture risk depleting the natural’ resource base on which the sustainability of that production depends. Biodiversity is both a critical component of the reductlons in natural capital wrought by industrial agriculture, and, when incorporated in agroecosystems, a key tool for developing sustainable alternatives. The term "farm diversification" encompasses a variety of transitions that can be implemented via potentially complementary ecological and economic modes at multiple levels of organization. Across a widely varied range of biophysical, cultural, and economic circumstances, diversified farms, as well as exchange networks in which they participate, often display increased stability and productivity. Stability and productivity are well recognized ecosystem functions that generally benefit human societies. We interpret farm diversification patterns in the context of recent developments in ecological theory and application, in which ecosystem stability and productivity benefit from increasing species diversity. We summarize the current state of ecological thinking on this diversity-ecosystem function hypothesis and present cases from several farming systems in which similar principles operate. In our analysis, farm diversification merits consideration and investigation as a key agroecological principle for building sustainability into systems of food and fiber. production.